Didactic strategies for the prevention of intestinal parasites in schoolchildren in the department of Antioquia, Colombia - Hernandez-Castro, Carolina; García-Tuberquia, Luis Alfonso; Medina-Lozano, Angélica Patricia; López-García, Diego; Botero-Garcés, Jorge Humberto; Agudelo-López, Sonia del Pilar (Universidad y Salud, 2025)
Introduction: Health education imparts knowledge, skills, and awareness about health issues to promote healthy behaviors that contribute to improving the quality of life. It empowers individuals to take responsibility for their own health and to take proactive steps to prevent disease and promote a healthy lifestyle. Objective: To implement didactic strategies for focused on health and on the prevention of intestinal parasitosis. Materials and methods: Descriptive observational longitudinal study in which educational institutions were selected in the Chocó-Magdalena and Norandina biogeographic provinces of the department of Antioquia. In each school, two groups were formed: one with health education intervention, which received pedagogical support with educational health strategies for six months, and another without any educational intervention. Results: In the schools of Chocó-Magdalena biogeographic province, a statistically significant difference (p = 0.000 y p = 0.008 for schools 1 and 2, respectively) was observed between the schoolchildren in the intervention group and those in the non-intervention group regarding their knowledge of parasite prevention. Conclusions: The adequate implementation of these educational strategies is essential to ensure a positive impact on the health and well-being of the population.